Changes in Body Mass Index and Physical Activity Predict Changes in Vitality During a Weight Loss Trial in Breast Cancer Survivors. Issue 12 (29th March 2018) - Kenzik, Kelly M; Demark-Wahnefried, Wendy; Ganz, Patricia A; Colditz, Graham; Rock, Cheryl L; Rogers, Laura Q
Abstract: Background: Breast cancer survivors rank fatigue (e.g., decreased vitality) as their number one concern affecting quality of life. Excess adiposity is associated with decreased vitality in breast cancer survivors, yet weight loss intervention trials report inconsistent effects on this parameter. Methods: This is a secondary analysis of the Exercise and Nutrition to Enhance Recovery and Good Health for You trial, in which 692 overweight or obese breast cancer survivors ≤5 years from diagnosis, initiated weight loss interventions, and completed assessments semi-annually for 2 years. Assessments included the Godin Leisure-Time Exercise Questionnaire and the SF-36 MOS vitality subscale as an inverse measure of fatigue. Multilevel structural equation models estimated the direct effects of physical activity on vitality and indirect effects through body mass index (BMI) changes. Results: Within-person findings show that at assessments with greater physical activity, BMI was significantly lower ( B = −0.07, p < 0.001) and vitality was higher ( B = 0.22, p < 0.001). However, there was no direct relationship between lower BMI and higher vitality ( B = −0.11, p = 0.262) after controlling for the relationship of physical activity with BMI and physical activity with vitality. The between-person indirect effect of physical activity change through BMI change to vitality was significant ( B = 0.03, p < 0.001). Participants whose physical activity was above the mean ( B = 0.37, p < 0.001) and whose BMI was below the mean ( B = −1.05, p < 0.001) were more likely to report greater vitality. Conclusion: Improvements in vitality are primarily associated with increases in physical activity rather than BMI changes in this trial. Vitality was lower among survivors with higher BMI, although within-individual changes in BMI had no effect on vitality. Physical activity and weight loss share mechanistic links to vitality with physical activity potentially increasing (e.g., in an additive or synergistic manner) the effect of BMI reduction on vitality. Abstract : Improvements in vitality are primarily associated with increases in physical activity rather than BMI changes in a weight loss intervention trial among breast cancer survivors.